RŪPESČIO ETIKA IR EMMANUELIS LEVINAS. - Bikauskaitė, Renata (Problems / Problemos, 2012)
In the context of the contemporary moral philosophy ethics of care appears to be quite a new discipline that lacks homogeneity and a well-defined moral vocabulary. Ethics of care is highly critical of the traditional ethical theories, though a few representatives, who are looking for well-established philosophical grounds, try to subsume it under the category of theory of virtue ethics. In this paper a different approach emerges which seeks to incorporate the ethics of care within the philosophy of Emmanuel Levinas. By analysing the ideas of Nel Noddings -- one of the best known representatives of the ethics of care -- and comparing them with the philosophy of Levinas an attempt is made to describe the overlaps between these two ethical discourses and explore the possibilities of their cooperation. This paper claims that Levinas' ethics provides a deeper normative ground for the naturalistic care ethics of Nodings and a wider philosophical context for its controversial notions.